THE EFFECT OF JOB INSECURITY AND WORK STRESS ON JOB SATISFACTION AND THEIR IMPLICATIONS FOR TURNOVER INTENTION ON PT CIPTAJAYA SEJAHTERA ABADI - Anastasia, Nadia; M. Havidz Aima; Hernawati W Retno Wiratih (Dinasti International Journal of Digital Business Management, 2022)
This study aims to find out the effect of job insecurity and work stress on turnover intentions and their implications for job satisfaction in PT Ciptajaya Sejahtera Abadi. This study is a quantitative study with a total of 142 employees. Data collection uses primary and secondary data. Technical data analysis uses path analysis methods (Path Models) with the help of SmartPLS version 3.2.9. From the results of this study showed that job insecurity has a positive and insignificant effect on turnover intentions. Job insecurity has a negative and significant effect on job satisfaction. Work stress negatively and significantly affects turnover intentions. Work stress has a positive and significant effect on job satisfaction. Job satisfaction shows a negative and insignificant effect on turnover intentions.